Emissões de dióxido de carbono durante a implantação de culturas em dois sistemas de preparo em latossolo vermelho do Rio Grande do Sul - Pes, Luciano Zucuni (2011)
In farming systems with annual crops, the crop establishment period is characterized by intense soil disturbance in conventional tillage (CT) or disturbance only in the sowing line, in case of no-tillage (NT). The soil tillage enhances the carbon dioxide (CO2) emissions whose should be investigated extensively during these short-term (scale days) that has implications in the carbon (C) dynamic in crop residues-soil-atmosphere system. This work was divided in two studies and they aimed quantify the role of main sources of soil C-CO2 (C labile soil and C crop-residues) and investigate the emission in different seasons. This study was carried out in a long-term experiment (installed in 1985) at Fundação Centro de Experimentação e Pesquisa (FUNDACEP) in a clay Typic Haplorthox. The first study evaluated the emissions of C-CO2 during 15 days of the spring 2009 and the fall 2010 using closed dynamic flow chamber with infrared analyzer. The crop residue input was black oat (Avena strigosa Schreber) and soybean (Glycine max (L.) Merr.) in spring 2009 and fall 2010, respectively. The second study evaluated the C-CO2 emissions during 23 days in fall 2007, 21 days in spring 2007, 15 days in spring 2009 and 15 days in fall 2010, also using closed dynamic chamber with infrared analyzer. The crop residues input were soybean, black oat + common vetch (Vicia sativa (L.) Walp.), black oat and soybean in fall 2007, spring 2007, spring 2009 and fall 2010, respectively. The temperature and soil moisture were also evaluated. The crop-residues were the main C-CO2 emission sources during the crop establishment period. Consequently, the soil C-labile exposed by tillage operations in the Oxisol had restricted contribution to the C-CO2 emissions. This result is probably related with organo-mineral C association that is frequently reported in soils with high Fe/Al oxides concentration and clay texture. In relation to the season effect, the crop-establishment period in spring had higher C-CO2 emissions than to fall.